A Systems Updating Approach For Proactive Health Monitoring Of Concrete Bridges - Rafiq, Meena Imran; Chryssanthopoulos, Marios K.; Onoufriou, Toula (My University, 2004)
Chloride induced corrosion of reinforcement embedded into concrete is the most common cause of deterioration in reinforced concrete bridges. Uncertainties associated with input parameters of its deterioration model strongly affect prediction of structural performance. A methodology has been developed that uses information obtained through health monitoring of structures to update their structural performance by reducing associated uncertainties. The proposed methodology is extended to incorporate information from multiple sensors at different locations to predict structural performance of the bridge (or its elements) with reduced uncertainty. Two different approaches have been identified for different scenarios to incorporate information obtained from multiple sensors. The advantages and limitations of the two approaches are discussed along with the scenarios where these approaches are applicable.
Keywords: Proactive Health Monitoring; Concrete Bridges